The advantages of water immersion colonoscopy in ambulatory service - Catinean, Adrian; Neag, Maria Adriana; Tulbure, Mihaela (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: The purpose of this prospective study was to compare patients’ discomfort during water immersion (WI) colonoscopy without sedation or available on request, with that of patients during air insufflation (AI) colonoscopy with sedation, in the ambulatory setting. Material and Methods: A prospective observational study was conducted in 100 patients who performed a colonoscopy between August 2015 and February 2016 in an Ambulatory Gastroenterology Center in Cluj-Napoca, Romania. They were divided into two branches A and B. Patients in Group A underwent a classic colonoscopy with AI and standard sedation (2 mg of midazolam and 50 mg of tramadol), while patients in Group B underwent an unsedated or on demand sedation colonoscopy with WI technique. Results: The patients in group A presented a higher discomfort (statistically significant) compared to those in group B, and had also the median total discomfort score higher than those in group B. The patients in group A had also a higher discomfort score after examination. The total time of examination was the same in the two groups, but in group B the progression to cecum time was 3 minutes lower than for those in group A. A greater discomfort of the patient was correlated with the longer time required to reach the cecum. Conclusion: In conclusion, WI colonoscopy is superior to AI technique in reducing insertion pain, progression-to-cecum time, minimizing sedation requirements and also in the willingness to repeat the technique. Cite this article as: Catinean A, Neag MA, Tulbure M. The advantages of water immersion colonoscopy in ambulatory service. Turk J Gastroenterol 2019; 30(7): 636-40.